The obesity-induced transcriptional regulator TRIP-Br2 mediates visceral fat endoplasmic reticulum stress-induced inflammation - Guifen Qiang (Nature Portfolio, 2016)
Visceral and subcutaneous fat are associated with different metabolic risk, but mediators of such depot specific effects are not very well known. Here the authors identify the transcriptional regulator, TRIP-Br2, as a regulator of endoplasmic reticulum (ER) stress-induced inflammatory responses specifically in visceral fat.